(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2020)
In a previous work (Camargo & Ried, 2016), we have argued that pharmacological practice has given rise to a new type of biopower (“molecular biopower”), with specific technologies and rationalities, distinguishing it from the biopower that Michel Foucault recognised in his later work. However, we also argued that another effect has been the creation of new forms of resistance. In this article, we present two specific models of resistance created by the apparatus of pharmacological power: one, inspired by pro-anorexia movements, which operates by resignifying the pathological categorization of anorexia using the drug Xenical; another, based on the experience outlined by Beatriz Preciado in her 2008 book Testo Junkie, which operates by overcoming legal, medical and moral limits to create a ground-breaking new identity by consuming prohibited doses of gel testosterone.